Endothelial Activation and Stress Index in Spondyloarthritis: Associations With Disease Duration and Clinical Characteristics - Altuğ Güner; Sümeyye Tuna Güner; Taner Dandinoğlu (The European Research Journal, 2026)
Objectives: Spondyloarthritis (SpA) is associated with increased cardiovascular morbidity driven by endothelial dysfunction, yet the role of the Endothelial Activation and Stress Index (EASIX) in this context is unclear. This study evaluated the association of EASIX with disease duration, activity, physical function, spinal mobility, and health-related quality of life in patients with SpA. Methods: Medical records of 69 patients with axial or peripheral SpA classified according to Assessment of SpondyloArthritis international Society criteria were reviewed. Clinical assessment included measures of disease activity (Bath Ankylosing Spondylitis Disease Activity Index [BASDAI] and Ankylosing Spondylitis Disease Activity Score based on C-reactive protein [ASDAS-CRP]), physical function (Bath Ankylosing Spondylitis Functional Index [BASFI]), spinal mobility (Bath Ankylosing Spondylitis Metrology Index [BASMI]), and health-related quality of life (12-Item Short Form Health Survey [SF-12]). EASIX was evaluated using correlation, subgroup, regression, ROC, and sensitivity analyses. Results: Disease duration was the only variable consistently associated with EASIX (r = 0.408, P < .001). Patients with disease duration >5 years had higher EASIX values (P = .001), and the association remained significant in multivariable analyses. Conversely, EASIX showed no relevant association with established indicators of disease activity, physical function, spinal mobility, or health-related quality of life. Conclusions: EASIX appeared to be associated with disease duration rather than current disease activity. These findings suggest that EASIX may reflect cumulative endothelial stress rather than contemporaneous inflammatory activity. Future prospective longitudinal studies are needed to examine this hypothesis.